Novel Biotechnologies for Biocontrol Agent Enhancement and Management - Vurro, Maurizio; Gressel, Jonathan; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
Weeds, insects, rodents, and pathogens are major problems in agricultural and urban environments, and there is a clear need to augment chemical methods of their control with biological methods. There has been limited success in doing so because of insufficient virulence of the host-specific organisms used. Naturally occurring biological agents are in evolutionary balance with their hosts, and attaining the level of control typically desired would lead to extinction of both the control agent and its host. The main scientists working with enhancing fungal, bacterial, virus and insect biological control agents on different targets present the latest progress in overcoming the barrier of insufficient virulence. This multi-disciplinary group, with backgrounds in different aspects of biotechnologies and crop protection review their own work and that of others, and describe the approaches being used, the successes and the barriers yet to overcome in an integrated manner.
BIOTECHNOLOGY IN CROP PROTECTION: TOWARDS SUSTAINABLE INSECT CONTROL -- BACTERIA AS BIOLOGICAL CONTROL AGENTS FOR INSECTS: ECONOMICS, ENGINEERING, AND ENVIRONMENTAL SAFETY -- BENEFITS AND RISKS OF USING FUNGAL TOXINS IN BIOLOGICAL CONTROL -- BIOCONTROL OF WEEDS WITH ALLELOPATHY: CONVENTIONAL AND TRANSGENIC APPROACHES -- SELECTING, MONITORING, AND ENHANCING THE PERFORMANCE OF BACTERIAL BIOCONTROL AGENTS: PRINCIPLES, PITFALLS, AND PROGRESS -- EXPLOITING THE INTERACTIONS BETWEEN FUNGAL ANTAGONISTS, PATHOGENS AND THE PLANT FOR BIOCONTROL -- THE MECHANISMS AND APPLICATIONS OF SYMBIOTIC OPPORTUNISTIC PLANT SYMBIONTS -- USING STRAINS OF FUSARIUM OXYSPORUM TO CONTROL FUSARIUM WILTS: DREAM OR REALITY? -- METARHIZIUM ANISOPLIAE AS A MODEL FOR STUDYING BIOINSECTICIDAL HOST PATHOGEN INTERACTIONS -- SCLEROTINIA MINOR-BIOCONTROL TARGET OR AGENT? -- FUSARIUM OXYSPORUM F. SP. STRIGA, ATHLETES FOOT OR ACHILLES HEEL? -- CONTROL OF SCLEROTIAL PATHOGENS WITH THE MYCOPARASITE CONIOTHYRIUM MINITANS -- BIOLOGICAL CONTROLS AND THE POTENTIAL OF BIOTECHNOLOGICAL CONTROLS FOR VERTEBRATE PEST SPECIES -- GENETICALLY ENHANCING THE EFFICACY OF PLANT PATHOGENS FOR CONTROL OF WEEDS -- INTERACTIONS OF SYNTHETIC HERBICIDES WITH PLANT DISEASE AND MICROBIAL HERBICIDES -- APPROACHES TO AND SUCCESSES IN DEVELOPING TRANSGENICALLY ENHANCED MYCOHERBICIDES -- FUNCTIONAL GENOMICS: FUNCTIONAL RECONSTITUTION OF PORTIONS OF THE PROTEOME IN INSECT CELL-LINES -- TAC-TICS: TRANSPOSON-BASED BIOLOGICAL PEST MANAGEMENT SYSTEMS -- FAILSAFE MECHANISMS FOR PREVENTING GENE FLOW AND ORGANISM DISPERSAL OF ENHANCED MICROBIAL BIOCONTROL AGENTS -- EPILOGUE: GETTING FROM HERE TO ETERNITY.
Keywords: LIFE SCIENCES; GENETIC ENGINEERING; AGRICULTURE; PLANT DISEASES; LIFE SCIENCES; AGRICULTURE; PLANT PATHOLOGY; GENETIC ENGINEERING